2011
DOI: 10.2174/092986611797642661
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Thermophilic Proteins with Pseudo Amino Acid Composition:Approached from Chaos Game Representation and Principal Component Analysis

Abstract: Comprehensive knowledge of thermophilic mechanisms about some organisms whose optimum growth temperature (OGT) ranges from 50 to 80 °C degree plays a major role for helping to design stable proteins. How to predict function-unknown proteins to be thermophilic is a long but not fairly resolved problem. Chaos game representation (CGR) can investigate hidden patterns in protein sequences, and also can visually reveal their previously unknown structures. In this paper, using the general form of pseudo amino acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…CTF is a fundamental group of features to recognize the interaction of RNA and proteins and was shown to be successful in the majority of published prediction tools [21,23,25,28]. Furthermore, CGR is an important group of features for protein studies and achieved remarkable results in many prediction tools [29][30][31][32][33]. Detailed comparisons with existing tools using RPI369 and RPI2241 demonstrated that the combinations of these two features indeed got achieved improvements, suggesting that our prediction model will be an important tool for RPI prediction.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…CTF is a fundamental group of features to recognize the interaction of RNA and proteins and was shown to be successful in the majority of published prediction tools [21,23,25,28]. Furthermore, CGR is an important group of features for protein studies and achieved remarkable results in many prediction tools [29][30][31][32][33]. Detailed comparisons with existing tools using RPI369 and RPI2241 demonstrated that the combinations of these two features indeed got achieved improvements, suggesting that our prediction model will be an important tool for RPI prediction.…”
Section: Introductionmentioning
confidence: 71%
“…2. Chaos game representation Chaos game representation (CGR) is another important method to formulate protein sequence and was also successfully used in many protein studies [29][30][31][32][33]. It originally applied the idea of Iterated Function System (IFS) from the fractal theory for generating CGR picture of DNA sequence in 1990 [35], and then was employed to generate CGR picture of protein sequence in 1997 [36].…”
Section: Features Of Proteins For Predictionmentioning
confidence: 99%
“…Therefore, it is natural to calculate box-counting dimensions of CGR pictures as an important feature. In fact, box-counting dimension has already been successfully employed as a significant fractal feature of DNA and protein sequences [19][20][21].…”
Section: Gpcr Familymentioning
confidence: 99%
“…In 1997, a similar CGR algorithm was presented by Basu, et al [16] to represent a protein sequence by using a 12-sided regular polygon, each vertex of which represents a class of amino acid residues on the basis of conservative substitutions. Up to present, CGR method has achieved some applications in the studies of bioinformatics [17][18][19][20][21]. Moreover, fractal dimensions (FD) are important features of highly irregular geometries.…”
Section: Introductionmentioning
confidence: 99%
“…CGR algorithm has many applications in the study of bioinformatics [14][15][16][17]. Among them, Yu et al [14] used CGR and multi-fractal analysis to construct a precise phylogenetic tree of bacteria; Yang et al [15] predicted protein structural classes by CGR algorithm and recurrence quantification analysis (RQA).…”
Section: Introductionmentioning
confidence: 99%